The Impact of Barcode Technology, Decision Making, and Resource Efficiency on Performance in Oil Palm Company - Zulham, Zulham; Aulia, Muhammad Reza; Suhendra, Rivansyah; Muzammil, Abdul; Fuqara, Fantashir Awwal (Universitas Teuku Umar, 2025)
This study aims to determine how barcode systems in oil palm firms impact overall performance, resource efficiency, and decision-making processes in the context of optimizing output. This study used 424 employees’sample data, which were gathered by proportional random sampling from April 2024 until June 2024. Partial least squares structural equation Modeling (PLS-SEM) was used to analyze the data. The Barcode System strongly influences resource efficiency and decision making. The overall performance is impacted by both resource efficiency and decision-making. In contrast to the Barcode System, which does not exert a direct influence on performance, its impact is indirect. This implies that the enhancement of performance is not automatically elevated by the Barcode System; instead, improvement must go through mediating variables, namely, resource efficiency and decision-making.